Study on HPLC fingerprint of Saposhnikovia divaricata lipophilic components and anti-aging effects - Xianwen Yue; Yang Xu; Bin Sun; Yali Shang; Zhuo Yu; Yingming Hu; Huiwei Bao; Hao Yue (Scientific Reports, 2024)
Abstract Saposhnikovia divaricata is commonly used in clinical practice as a heat-clearing and detoxifying traditional Chinese medicine. Current research on Saposhnikovia divaricata has mostly focused on chromones, while studies on its lipophilic parts remain scarce. In this study, samples of the lipophilic components of Saposhnikovia divaricata (SDL) from different regions in China were collected to establish an HPLC fingerprint. The quality of SDL was evaluated through chemical pattern recognition and multi-component content determination. Furthermore, using the Caenorhabditis elegans (C. elegans) model, the anti-aging ability of SDL was preliminarily studied. In the HPLC fingerprints of 11 batches of SDL, 19 common peaks were identified, and 4 components were characterized as follows: peak 14, linolenic acid (ALA); peak 15, docosahexaenoic acid (DHA); peak 16, linoleic acid (LA); peak 17, oleic acid (OA). The similarity of the fingerprint ranged from 0.704 to 0.929. The results indicate that the content of ALA, DHA, LA, and OA are 0.040–0.440 mg/g, 0.003–0.116 mg/g, 1.047–6.460 mg/g, and 0.040–0.294 mg/g, respectively. HCA analysis divided 11 batches of SDL into two categories, and PCA analysis extracted 6 principal components with a cumulative contribution rate of 85.91%. The anti-aging ability of the SDL was proved by measuring the lifespan, reproductive capacity, body length, mobility, lipofuscin content, and heat stress resistance of C. elegans. The combination of high-performance liquid chromatography fingerprint and chemical pattern recognition for multi-component content determination is a reliable, comprehensive, and promising evaluation of the quality of SDL. The confirmation of SDL’s anti-aging ability provides the possibility for the research of Saposhnikovia divaricata in the field of healthy food and cosmetics.